Production Risk Analysis of Shrimp Petis in UD. Dewi Sri Ayu, Banyuwangi Regency of East Java - Rezky Aditya Nugraha; Pudji Purwanti; Mochammad Fattah (Faculty of Fisheries and Marine Science, Brawijaya University, 2018)
Prawn shrimp production business is inseparable from the constraints faced, namely the form of production risks that can hamper in running the business of prawn shrimp production. UD Dewi Sri Ayu is one of the businesses that produce prawn shrimp that has been engaged in the fishery industry since 2000. The purpose of this research is to identify sources of production risk, to analyze how the value of probability and the impact of risk caused by sources of risk, and how alternative strategies for handling production risk that can be done by UD Dewi Sri Ayu. The research method used descriptive method to identify sources of production risk in UD Dewi Sri Ayu, z-score method to calculate probability value and Value at Risk method to calculate risk impact. Methods of data collection in this study is to make observations, interviews, and documentation. The result of identification has been found four kinds of source of production risk in prawn shrimp production activity at UD Dewi Sri Ayu, that is source of risk caused by mushroom (dewded packaging) having probability value and biggest impact loss, mushroom (petis not ripe perfect) human resource error (hard petty texture), and lastly the human resource error (taste of acid petition) that has the least probability and impact loss value. Alternative strategies for handling production risks can be done in two ways: preventive strategies and mitigation strategies. The advice that can be given to UD Dewi Sri Ayu is in handling production risk better done gradually by looking at the level of risk from sources of risk that exist.